DigitArq: creating a historical digital archive - Ferreira, Miguel (2004)
In this paper we present the steps followed in a project called DigitArq that aimed at building a centralised repository for archival finding aids. At the Arquivo Distrital do Porto, finding aids existed in several different formats and media. Migration was used to convert all the finding aids into a single normalised format based on an international standard – the EAD/XML. After migration, archival management software was developed to maintain the collected information and assist archivists in the creation of new finding aids. Archival finding aids are described by hierarchical structures which can easily be described in XML but present interesting issues while using Relational Databases. The relational data model employed is described in detail together with the reasons that made us choose this kind of implementation. Some statistics of the migration process will also be discussed in order to give the audience some insight about the legacy problem and the necessary investment to deal with it.